1958
DOI: 10.1103/physrev.110.682
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and Inelastic Scattering of 18-Mev Alpha Particles from Neon, Argon, and Xenon

Abstract: NEEDof protons, and perhaps the parameters in the leveldensity formula need to be specially adjusted for this situation. It would seem that much more experimental evidence needs to be obtained to discover systematics which may exist. CONCLUSIONThe results of the present experiment suggest that the statistical theory of nuclear reactions describes adequately, at least, the shapes of the energy spectra of light particles from nitrogen-induced reactions at zero degrees. Angular distributions and experiments onThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1961
1961
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…It turns out that the limited angular range of the angular distributions by Bucurescu et al [95] is not sufficient to derive the total reaction cross section σ reac from these data. The angular distribution of Seidlitz et al [96] covers the full angular range; however, at forward angles the measured cross section is almost twice the Rutherford cross section of pointlike charges. Therefore, Gaul et al [75] have suggested to scale the angular distribution by Seidlitz et al by a factor of 0.55; a similar scaling factor of 0.57 is suggested from the best fit obtained in this work.…”
Section: 90]mentioning
confidence: 97%
See 2 more Smart Citations
“…It turns out that the limited angular range of the angular distributions by Bucurescu et al [95] is not sufficient to derive the total reaction cross section σ reac from these data. The angular distribution of Seidlitz et al [96] covers the full angular range; however, at forward angles the measured cross section is almost twice the Rutherford cross section of pointlike charges. Therefore, Gaul et al [75] have suggested to scale the angular distribution by Seidlitz et al by a factor of 0.55; a similar scaling factor of 0.57 is suggested from the best fit obtained in this work.…”
Section: 90]mentioning
confidence: 97%
“…Therefore the following study is restricted to the data by Seidlitz et al [96] and the data at the lowest energies by Bucurescu et al [95]. It turns out that the limited angular range of the angular distributions by Bucurescu et al [95] is not sufficient to derive the total reaction cross section σ reac from these data.…”
Section: 90]mentioning
confidence: 99%
See 1 more Smart Citation
“…The α scattering on some light and medium-heavy nuclei exhibit strong enhancement of cross section at backward angles [i.e., the so-called anomalous large angle scattering (ALAS)]. This phenomenon brought considerable interest and was explained by various approaches (e.g., modified WoodsSaxon potential, L-dependent potential, folding potential, α exchange, Regge poles, and so on [1][2][3][4][5][6][7][8][9][10][11][12]). …”
Section: Introductionmentioning
confidence: 98%
“…For the elastic α+ 20 Ne scattering, there have been the measured differential cross sections over complete angular range: in the lower incident energy region, the angular distributions at E α = 16.8 MeV [3], 18.0 MeV [4], 20.2-23.0 MeV [5], and 25.8-31.1 MeV [6]; in higher incident energy region, the very detailed measured angular distribution at E α = 54.1 MeV [7]. All these experimental angular distributions exhibit remarkable ALAS features.…”
Section: Introductionmentioning
confidence: 99%